Therapeutic landscapes of home: Exploring Indigenous peoples' experiences of a Housing First intervention in Winnipeg. (December 2015) - Alaazi, Dominic A.; Masuda, Jeffrey R.; Evans, Joshua; Distasio, Jino
Abstract: In this paper, we explore Indigenous perspectives of culture, place, and health among participants in a landmark Canadian Housing First initiative: At Home/Chez Soi (AHCS) project. Implemented from 2009 to 2013 in Winnipeg and four other Canadian cities, AHCS was a multi-city randomized control trial that sought to test the effectiveness of Housing First as a model for addressing chronic homelessness among people living with mental illnesses. As Winnipeg's homeless population is over 70% Indigenous, significant efforts were made to accommodate the culturally specific health, spiritual, and lifestyle preferences of the project's Indigenous participants. While a daunting challenge from an intervention perspective, Winnipeg's experience also provides a unique opportunity to examine how Indigenous participants' experiences can inform improved housing and mental health policy in Canada. In our study, conducted independently from, but with endorsement of the AHCS project, we utilized a case study approach to explore the experiences of the project's Indigenous participants. Data were collected by means of in-depth qualitative interviews with Indigenous participants (N = 14) and key informant project staff and investigators (N = 6). Our exploratory work demonstrates that despite relative satisfaction with the AHCS intervention, Indigenous peoples' sense of place in the city remains largely disconnected from their housing experiences. We found that structural factors, particularly the shortage of affordable housing and systemic erasure of Indigeneity from the urban sociocultural and political landscape, have adversely impacted Indigenous peoples' sense of place and home. Highlights: Indigenous peoples' sense of place relating to home is qualitatively unique. Connection to land and community is central to Indigenous peoples' sense of home. Indigenous peoples' sense of place in the city is constrained by structural factors.